2016
DOI: 10.2169/internalmedicine.55.6874
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Mucosa-associated Lymphoid Tissue Lymphoma with Spontaneous Regression after Computed Tomography-guided Needle Biopsy: A Case Report and Summary of 8 Reported Cases

Abstract: A 72-year-old woman was admitted to our hospital with a solitary right lung nodule. She had no symptoms and no abnormal physical findings except for bladder cancer. Tumor markers were mildly elevated but no other abnormal laboratory data were found. The nodule was diagnosed to be pulmonary mucosa-associated lymphoid tissue lymphoma on computed tomography-guided needle biopsy. Thereafter, she first underwent surgery for bladder cancer. The lung nodule was found to have slightly increased at three months and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…pMALToma generally has a favorable prognosis due to the prospect of spontaneous regression. The survival rate has been reported to be 91%, 59%, and 53% at one year, five years, and ten years respectively [ 17 , 20 ]. Advanced histopathological stage and presence of amyloid in tumor confer a poor prognosis, as does age greater than 70 years, advanced stage IV disease, and elevated beta-2 microglobulin [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…pMALToma generally has a favorable prognosis due to the prospect of spontaneous regression. The survival rate has been reported to be 91%, 59%, and 53% at one year, five years, and ten years respectively [ 17 , 20 ]. Advanced histopathological stage and presence of amyloid in tumor confer a poor prognosis, as does age greater than 70 years, advanced stage IV disease, and elevated beta-2 microglobulin [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have now demonstrated that eradication of H. pylori in patients with low-grade gastric MALT lymphoma can result in regression of the tumor [ [23] , [24] , [25] , [26] , [27] ]. There have also been several reports of patients with NHL showing regression after a biopsy, indicating that trauma, including a biopsy, is related to regression [ 28 , 29 ]. The leading hypothesis regarding spontaneous regression in relation to NHL involves modulation of the host immune systeme to viral or bacterial infection and the anti-inflammatory effect of macrolide-induced apoptosis of lymphocytes via the downregulation of overexpressed Bcl-xL [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average duration of SR has been reported to be thirteen months 5 . For aggressive lymphomas, such as DLBCL, SR may rarely occur, although SR has been commonly reported for low-grade lymphomas such as follicular lymphoma and mucosal-associated lymphoid tissue lymphoma 3 , 6 . SR has been observed mostly for extranodal lymphoma in regions, such as the breast 7 - 9 and skin, 10 but rarely for nodal lymphoma 3 .…”
Section: Discussionmentioning
confidence: 99%